2000
DOI: 10.1111/1467-6494.00098
|View full text |Cite
|
Sign up to set email alerts
|

The Fruits of Their Labors: A Longitudinal Exploration of Parent Personality and Adjustment in Their Adult Children

Abstract: This longitudinal study of several aspects of parenting examines how children "turn out" as adults. Ratings of adjustment (educational and occupational attainment as well as social and emotional maturity) in young adult children (aged 25-37) were made on the basis of information from 64 mothers who were participants in a longitudinal study of women's lives. As hypothesized, mothers who were demanding yet responsive, sensitive, and psychologically mature at ages 27 and 43 had children with higher overall adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…Thus, the present findings substantiate previous indications of a positive association between parental warmth and adolescent psychological adjustment and coping, as well as parents' behavioural control and their children's selfregulation and compliance, which lead to better mental health (Aunola & Nurmi, 2005, Barber et al, 1994, Buschgens et al, 2010, Solomon, 2000, Yap & Jorm, 2015. The combination of both parenting dimensions (i.e., warmth and behavioural control) has been proposed as particularly supportive of adolescent mental health by different studies (this combination has been termed "authoritative parenting"; Calders et al, 2020, Steinberg, 2001.…”
Section: Parenting and Adolescent Mental Health Problemssupporting
confidence: 89%
“…Thus, the present findings substantiate previous indications of a positive association between parental warmth and adolescent psychological adjustment and coping, as well as parents' behavioural control and their children's selfregulation and compliance, which lead to better mental health (Aunola & Nurmi, 2005, Barber et al, 1994, Buschgens et al, 2010, Solomon, 2000, Yap & Jorm, 2015. The combination of both parenting dimensions (i.e., warmth and behavioural control) has been proposed as particularly supportive of adolescent mental health by different studies (this combination has been termed "authoritative parenting"; Calders et al, 2020, Steinberg, 2001.…”
Section: Parenting and Adolescent Mental Health Problemssupporting
confidence: 89%
“…These observations suggest that parental reflectivity during adolescence paves the way for social adjustment during adulthood (Solomon 2000). However, our findings suggest that parental reflective function might carry both benefits and costs.…”
Section: Discussionmentioning
confidence: 56%
“…Researchers have ignored the possibility that E and N might jointly contribute to the quality of child-rearing. Yet, authoritative parents are likely to be characterized not only by high E but also by low N. Empirical evidence has been provided by Solomon (2000) who showed that mothers whose children turned out well adjusted adults were high in gregariousness, perceptiveness, cheerfulness, and self-confidence, whereas they were least characterized as brittle, aloof, over-reactive, frustrated, anxious, or moody. At issue is whether high E in combination with emotional unstability (high N) is related to a particular type(s) of parenting.…”
mentioning
confidence: 99%